Kepribadian Guru Generasi Gen Z: Kajian Teoritis Tentang Karakteristik dan Implikasinya Dalam Lingkungan Sekolah - Mursidin; Fatiya Tsabita Mujahidah; Nasywaah Alzahrah Hidayat Nur; Natia Khoirunnisa (Bildung: Jurnal Ilmu Pendidikan, 2026)
This study aims to comprehensively understand the personality traits of Generation Z teachers in the educational context. The primary focus is to identify the personality traits of Generation Z teachers according to theory and then examine how these traits relate to the roles and responsibilities of teachers in the school environment. This study also aims to analyze the implications of these traits on the dynamics of learning and professional interactions in schools. Furthermore, this study seeks to explain the potential strengths and weaknesses of Generation Z teachers' personalities, which could impact overall educational performance. This study uses a descriptive qualitative approach based on a literature review to analyze theories and scientific findings on Generation Z teacher personality. Data were obtained from primary sources such as generational theories, personality theories, and related journals, as well as secondary sources such as books, educational reports, and official documents. Data were collected through a structured literature search and analyzed using content and thematic analysis to identify key concepts and develop a comprehensive synthesis without field data collection. Generation Z teachers' personalities significantly influence education through their technological skills, creativity, and open communication, which support innovative learning. Their rapid adaptation helps them navigate curriculum changes and digital demands. However, their tendency to be easily distracted, their dependence on technology, and their sensitivity to work pressure can hinder their professionalism. These characteristics also influence interactions in schools. With the right mentoring and support, the potential of Gen Z teachers can be optimized to improve the quality of education.